HUBUNGAN ANESTESI SPINAL DENGAN SHIVERING PADA PASIEN POST OPERASI DI RUANG RECOVERY ROOM - nazmi, Annisa; Fajri andi rahmawan; Fransiska Erna Damayanti (Jurnal Keperawatan Muhammadiyah, 2026)
Objective: Post-anesthesia shivering is a common side effect that can cause complications due to the resulting increase in oxygen consumption. Oxygen consumption increases fivefold and can reduce arterial oxygen saturation so that if shivering is not treated it can cause an increased risk of myocardial ischemic disease. This study aims to determine the relationship between Spinal Anesthesia and Shivering in post-operative patients in the Recovery Room. Methods: The research design used was Cross Sectional with 50 respondents using Purposive Sampling technique. Using the Bedside Shivering Assessment score (BSAS) and Bromage score instruments, then analyzed using the Spearman rank test. Results: The results of the research showed that the bromage score for spinal anesthesia was 2, namely 24 respondents or (48%) and most of the shivering grades experienced by respondents were grade 1, 17 respondents or (34%). There is a relationship between spinal anesthesia and shivering with a value (P value) of 0.000. The correlation results obtained were (r=0.86), where the figure was in the correlation range (0.80-1.000), that is, the level of relationship between the two correlation variables had a very strong relationship. Conclusion: Observation of post-operative patients should be included in the operating room to prevent prolonged post-anesthesia shivering